Extreme photopolarimetric behaviour of the blazar AO 0235+164 - Cellone, Sergio Aldo (2007)
We present optical photopolarimetric observations with high temporal resolution of the blazar AO 0235+164. Our data, the first to test the photopolarimetric behaviour of this object at very short time-scales, show significant micro-variability in total flux, colour index, linear polarization degree and position angle. Strong inter-night variations are also detected for these parameters. Although no correlation between colour index and total flux was found, our data seem to support the general bluer-when-brighter trend already known for this object. The polarization degree, in turn, shows no correlation with total flux, but a clear trend in the sense that colour index is redder (the spectrum is softer) when the measured polarization is higher.